Presence and (dis)connectedness – the influence of smartphones usage on human–nature and human–human interactions in outdoor studies - van Kraalingen, Imre; Beames, Simon (Frontiers in Education, 2024)
Interactions between students and nature and students and their peers are central to learning processes in outdoor studies programs. This paper draws on symbolic interactionist social theory to interpret participants’ experiences of smartphone usage and its impact on human–nature and human–human interactions. The findings are derived from a collective case study using semi-structured interviews with educators and focus group interviews with students enrolled in outdoor studies programs in Norway. Two primary themes were identified through reflexive thematic analysis: perceptions of nature and attentiveness to peers. Each of these themes illustrates the fluctuating presence and (dis) connectedness of students and the implications of this for learning out-of-doors. On the one hand, the findings suggest that the use of smartphones reduces students’ sensory perception of nature and their attentiveness to interactions with their peers. On the other hand, smartphones and their access to online networks can contribute to the continuity of learning experiences between indoor and outdoor learning, as well as beyond the formal learning environment. Taken together, this inquiry offers new insights into the challenges of tertiary level teaching and learning outdoors in spaces that are mediated (at times) by interactions with smartphones and associated media infrastructures.